2010
DOI: 10.1056/nejmoa0905848
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Initiation of Antiretroviral Drugs during Tuberculosis Therapy

Abstract: Despite high mortality rates in tuberculosis patients with HIV co-infection, there is continued controversy on when to initiate antiretroviral therapy (ART) in these patients. Methods-We conducted an open-label randomized controlled trial in Durban, South Africa to determine optimal timing of ART initiation in relation to TB treatment. Acid-fast bacilli (AFB) smear positive tuberculosis patients with HIV infection and CD4+ counts <500 cells/mm 3 (n=642) were randomized to one of two integrated treatment arms (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
376
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 568 publications
(409 citation statements)
references
References 18 publications
22
376
2
2
Order By: Relevance
“…[9] We also found that 71% of patients were HIV co-infected, which is slightly higher than the national average of 61%. [1] While this rate is very high, the proportion of TB patients starting treatment with an unknown HIV status has dropped considerably in recent years (from 41% in 2009 to just 7% in 2014) and the proportion of HIVpositive TB patients on ART has increased dramatically (from 16% in 2009 to 79% in 2014).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…[9] We also found that 71% of patients were HIV co-infected, which is slightly higher than the national average of 61%. [1] While this rate is very high, the proportion of TB patients starting treatment with an unknown HIV status has dropped considerably in recent years (from 41% in 2009 to just 7% in 2014) and the proportion of HIVpositive TB patients on ART has increased dramatically (from 16% in 2009 to 79% in 2014).…”
Section: Discussionmentioning
confidence: 63%
“…[4] Increasing CD4 counts [8] and timely ART initiation are known to reduce mortality during TB therapy. [9] With SA guidelines prioritising the initiation of all HIV/TB co-infected patients (regardless of CD4 count or clinical staging), [3] increases in ART coverage among TB patients are likely to continue, helping drive reductions in TB mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate remains high even after completion of TB treatment, probably due to HIV disease. [6] Scaling up antiretroviral therapy (ART) to all HIV-infected TB patients is required to reduce HIV-related mortality among TB patients.…”
Section: Treat Tbmentioning
confidence: 99%
“…Initiating ART while on TB treatment saves lives, regardless of CD4 + count, and among persons with CD4 + counts <50 cells/µl, initiating ART soon after initiating TB treatment is essential to reduce mortality. [6,25] Decentralisation of ART services to primary healthcare clinics and integration with TB services have resulted in increasing numbers of TB patients initiating ART. In 2012, only 54% of HIV-positive TB patients were initiated on ART, [1] highlighting the need to scale up ART for TB patients further by scaling up nurse-initiated and managed ART training for all professional nurses.…”
Section: Tb/hiv Integrationmentioning
confidence: 99%
“…Early initiation of antiretroviral therapy (ART) during TB therapy substantially reduces TB-related morbidity and mortality rates for coinfected patients (2,3), and the World Health Organization recommends that ART be started as soon as possible but within 8 weeks after the initiation of TB therapy (4). Simultaneously, the global emergence and increased dissemination of multidrug-resistant (MDR) and extensively drug-resistant (XDR) TB have increased the need for novel anti-TB drugs with new mechanisms of action.…”
mentioning
confidence: 99%